Una pedagogía visceral: experiencias de cuidado y trabajo emocional de profesoras en la periferia carioca - Bello Ramírez, Alanis (Educación y Ciudad, 2020)
In this research article, we analyze the experiences of working black teachers in schools affected by armed violence in the peripheries of the city of Rio de Janeiro, from a methodological feminist perspective of situated knowledges. Through this point of view, we account for a school routine marked by shootings, marginalization and exposure to the death of school agents. In this context we appropriate the notion of "visceral pedagogy" to show how through care and emotional work, teachers configure spaces for survival, attention to emotional damage and the affirmation of life in the midst of a reality configured by logics of gender, race and class domination.